Y(OTf)3-Catalyzed Cascade Propargylic Substitution/Aza-Meyer–Schuster Rearrangement: Stereoselective Synthesis of α,β-Unsaturated Hydrazones and Their Conversion into Pyrazoles - Liu, Wenfei; Wang, Han; Zhao, Haiying; Li, Baoguo; Chen, Shufeng (Synlett, 2015)
A straightforward and concise method for the highly stereoselective synthesis of α,β-unsaturated hydrazones by the Y(OTf)3-catalyzed cascade propargylic substitution/aza-Meyer–Schuster rearrangement reaction of tertiary propargylic alcohols and p-toluenesulfonyl hydrazide under an air atmosphere is developed. A series of α,β-unsaturated hydrazones have been synthesized from simple and readily available starting materials in good yields. Furthermore, the obtained α,β-unsaturated hydrazones are converted into pyrazoles in the presence of LiOt-Bu.
Keywords: propargylic alcohols; aza-Meyer–Schuster rearrangement; Y(OTf)3; α,β-unsaturated hydrazones; pyrazoles